The Mediating Role of Communication Beliefs and Marital Self-Regulation in the Relationship between the Dyadic Perspective Taking of the Spouse and Marital Conflicts - Abdolsaleh Khazaei; Ali Pouladi Rishehri; Javad Aynypour (پژوهش‌های کاربردی روانشناختی)
The objective of this study was to investigate the mediating role of communication beliefs and marital self-regulation in the relationship between spousal cognitive perspective and marital conflicts in women who visited counseling centers in Bushehr city in 2021. A random sample of 250 individuals was selected from the statistical population of 487 married women who used counseling centers in Bushehr city. The data were collected using the Self Dyadic Perspective Taking Scale (SDPT), Relationship Beliefs Inventory (RBI), Behavioral Self-Regulation Scale (BSR), and Marital Conflict Questionnaire (MCQ) in a correlational study. SPSS and Amos software version 21 were employed to analyze the collected data using the structural equation modeling (SEM) method. The results indicated that the cognitive perspective of the spouse had a direct impact on communication beliefs (β = 0.64), marital self-regulation (β = 0.55), and marital conflicts (β = 0.29), and an indirect effect on marital conflicts through communication beliefs (β = 0.18). Therefore, it can be inferred that the spouse cognitive perspective predicts marital conflicts through the mediation of communication beliefs and marital self-regulation. It is recommended that family counselors, psychologists, and educational specialists concentrate on improving marital self-regulation and modifying communication beliefs between couples in order to mitigate marital conflicts.